(3GdoYeOI aj UfGYI GdTYQ hfbOgs - (3GdMSf Hf QTjb GdbjQhGfj, CHh Ydj , GHf QTjb,J (B463 (3g` s
(3ChdgG (B:s
(3HGH aj CTYGQ GdNdaGA hGdbVGI GdabgGA, hef Pdc bhd CHj HcQ GdUOjb QVj Gddg Yfg bGdhG hGSeg YHOGddg Hf YKeGf, hjbGd YJjb dbH dg s
(3BNQgG (B:s
(3hQRFJg QhVI jQhb, hde CSeY HQhV jSYi Ydi GdbOe s
(3fSNI QGHYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B191 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B225s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B51 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1169s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdCOHs